Aplikasi Sistem Pakar untuk Mengidentifikasi Penyakit pada Hamster (Cricetinae) dan Saran Pengobatannya Menggunakan Metode Backward Chaining - Susi Kurniasih; Dwi Aryanto; Agung Purwo Wicaksono (Department of Informatics Engineering, Universitas Muhammadiyah Purwokerto, 2012)
The expert system is a computer program that can replicate the thinking process and expert knowledge to solve specific problems. In this case, the expert system is used by breeder and hamster lovers to detect diseases that commonly infect hamsters. The purpose of this research is to build the expert system as a tool to identify and provide advice on the appropriate treatment of hamster disease. The expert system was made by backward chaining inference method and designed using PHP as the programming language. The working process of this expert system is the user search based on the visible symptoms and at the end the users will get the name tracking the disease and its treatment advice. With the expert system, the user, specifically hamster lovers, are expected to save cost and time, in this regard to the cost of the vet to diagnose and treat hamster diseases